The Relationship Between Medication Compliance and Body Mass Index in Elderly Patients with Hypertension - Astuti, Widya (Open Access Health Scientific Journal, 2025)
Background: Hypertension is a major public health concern, especially among the elderly, as it increases the risk of cardiovascular diseases, stroke, and kidney failure. Effective management requires strict medication compliance, but adherence remains low due to factors like forgetfulness, complex regimens, and side effects. This study aimed to analyze relationship between body mass index and medication compliance in hypertensive patients.Methods: This cross-sectional study examined the relationship between medication compliance and Body Mass Index (BMI) in 76 elderly hypertensive patients. Data were collected using the Morisky Medication Compliance Scale (MMAS-8), BMI measurements, and medical records. Statistical analysis, including the Chi-Square test, was conducted using SPSS.Results: The findings a significant relationship between Body Mass Index (BMI) and medication compliance, showing that individuals with normal BMI (28.9%) have higher adherence (25.0%) compared to those who are underweight (39.5%) or obese/overweight (31.6%), with the latter group exhibiting the highest rate of poor compliance (52.6%) and none adhering well, emphasizing the statistical significance of this relationship (P= 0.000) and the need to understand how health-related behaviors interact with physical health indicators like BMI.Conclusion: This study shows a significant relationship between Body Mass Index and medication compliance, with individuals who are obese or overweight having the highest rates of poor compliance, while those with normal BMI demonstrate better adherence, possibly due to fewer health-related complications.